2020
DOI: 10.1186/s13287-020-01762-z
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based therapies for ischemic stroke: a systematic review and meta-analysis of clinical trials

Abstract: Recently, extensive researches about stem cell-based therapies for ischemic stroke have been published; our review evaluated the efficacy and safety of stem cell-based therapies for ischemic stroke. Our review was registered on PROSPERO (http://www.crd.york.ac.uk/PROSPERO), registration number CRD42019135805. Two independent observers searched PubMed, EMBASE, Cochrane Library (Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials), and Web of Science (Science Citation Index Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 61 publications
1
28
1
2
Order By: Relevance
“…Our results support the view that the immunosuppressive capacity of BM-derived MSCs is not innate but most likely induced under inflammatory conditions in situ [85]. In our view, there is no doubt that BM-derived MSCs have a beneficial effect in stroke as reviewed for both rodent and human stroke trials [1,65,[86][87][88]; however, further details are needed in order to understand the mechanism of these cells poststroke fully.…”
Section: Discussionsupporting
confidence: 84%
“…Our results support the view that the immunosuppressive capacity of BM-derived MSCs is not innate but most likely induced under inflammatory conditions in situ [85]. In our view, there is no doubt that BM-derived MSCs have a beneficial effect in stroke as reviewed for both rodent and human stroke trials [1,65,[86][87][88]; however, further details are needed in order to understand the mechanism of these cells poststroke fully.…”
Section: Discussionsupporting
confidence: 84%
“…These considerations are further fueled by the fact that clinical trials e.g. on cerebral infarction and chronic ischemic heart disease and stem cell therapy have yielded mixed results 39 , 40 . Beyond cardiovascular disease, recent studies also demonstrated that transplanted MSCs are mainly trapped in the lung, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…using IV transplantation of allogenic MSCs was successful, showing significant behavioral improvement in their Barthel Index (BI) scores, which measures a patient's ability to function in daily life [ 42 ]. Fortunately, all these clinical trials were safe in patients, showing significant improvement from older clinical trials that had severe adverse effects [ 43 ]. The most likely reason for the inconsistent results is the small size of these trials, which leads to a risk of bias [ 43 ].…”
Section: Future Treatments: Limiting Reperfusion Damage and Recovering From Ischemic Strokementioning
confidence: 99%
“…Fortunately, all these clinical trials were safe in patients, showing significant improvement from older clinical trials that had severe adverse effects [ 43 ]. The most likely reason for the inconsistent results is the small size of these trials, which leads to a risk of bias [ 43 ]. Two phase III clinical trials are currently being conducted (MASTERS-2 and TREASURE), so a better understanding of MSC efficacy may be reached soon [ 44 ].…”
Section: Future Treatments: Limiting Reperfusion Damage and Recovering From Ischemic Strokementioning
confidence: 99%